DFT study of adsorption and diffusion of Mg, K, Ca over monolayer antimonene. Issue 1 (March 2021) - Upadhyay, S; Srivastava, P
Abstract: Density Functional theory (DFT) based calculations are carried out to investigate adsorption and diffusion properties of Magnesium (Mg), Potassium (K) and Calcium (Ca) over single layer antimony (Sb) i.e. antimonene. Ca has highest value of absolute adsorption energy followed by K and Mg respectively. Charge transfer is greater in case of K adsorbed antimonene as compared to both of the other metals. This affects the electronic properties such as bandstructure and density of states. Antimonene is semiconducting in its pristine form. The adsorption of K leads to a shift to metallic nature, whereas Mg and Ca adsorption still maintain the semiconducting nature after reducing the bandgap. Diffusion of these metals shows that K can easily diffuse through the antimonene surface as compared to the Mg and Ca. The value of diffusion barrier for Mg, K and Ca is 0.30, 0.12 and 0.43 eV respectively. The effective adsorption and charge transfer along with low values of diffusion barrier suggests that phosphorene can be explored further as potential candidate for metal-ion batteries.